Assessing The Satisfaction of Malaysian Undergraduate Students in Virtual Flipped Classroom (VFC) During Covid-19 Pandemic - Masrom, Umi Kalsom; Nik Mohd Alwi, Nik Aloesnita; Tarmidi, Mahlindayu (IATED, 2022)
The move towards virtual education due to the COVID-19 pandemic has led to various studies searching to improve the new learning environment. This study investigates the student satisfaction determinants in a Virtual Flipped Classroom (VFC) setting and explores the mediating effects of skills on student satisfaction. The data were collected through an online survey among business management undergraduate students and examined the learner-content interaction, learner-instructor interaction, learner-learner interaction, access to information and learning resources, learning effect, and learner skills. Based on the Structural Equation Model (SEM) analysis, the study found no determinants of student satisfaction and no mediating effects of skills on student satisfaction. Conversely, a significant effect was found between VFC and skills. This study will aid educators to enhance student satisfaction in online classes, particularly during the pandemic.